Turning the Tide on Hepatitis C Virus–Related Liver Transplantation: The Return on Investment in Hepatitis C Virus Treatment in Australia and New Zealand. Issue 2 (10th November 2021) - Howell, Jess; Majumdar, Avik; Fink, Michael A.; Byrne, Mandy; McCaughan, Geoff; Strasser, Simone I.; Crawford, Michael; Hodgkinson, Peter; Stuart, Katherine A.; Tallis, Caroline; Chen, John; Wigg, Alan; et al.
Abstract : Introduction of universal access to direct‐acting antiviral (DAA) therapy for hepatitis C virus (HCV) in Australia and New Zealand on March 1 st, 2016, has had a major impact on the number of people with chronic HCV infection, but the impact on liver transplantation rates is unknown. We conducted a retrospective registry study including all adult liver transplantations from the Australia and New Zealand Liver and Intestinal Liver Transplant Registry (ANZLITR) data set. Interrupted time series analysis determined the impact of DAAs in 2016 on the number of HCV liver transplantations per year. Cox regression analysis was used to determine the impact of DAAs on post–liver transplantation survival. Between January 1, 1990, and December 31, 2019 5318 adult liver transplantations were performed, and 29% (1531) were for HCV infection. Prior to the introduction of DAAs, there was a mean increase of 3.5 adult liver transplantations performed for HCV per annum, but between 2016 and 2019 there was a mean decrease of 7.9 adult liver transplantations per annum ( P  < 0.001). Similarly, the proportion of liver transplantations performed for HCV increased from 9% (1990) to 33% in 2016 and then fell to 23% in 2019 ( P  < 0.001). The number and proportion of patients with HCV added to the liver transplantation waiting list also fell in 2016 ( P  < 0.001) when compared with other indications. The introduction of DAAs was associated with a 31% reduction in death after liver transplantation, adjusted for age at transplant and hepatocellular carcinoma (HCC; hazard ratio [HR], 0.69; 95% confidence interval [CI], 0.48‐0.99; P  = 0.047). The number of adult liver transplantations performed for HCV‐related liver cirrhosis and HCC has reduced since the introduction of universal access to DAAs in 2016 in Australia and New Zealand.